1994
DOI: 10.1002/ppul.1950180502
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary mechanics in ventilated preterm infants with respiratory distress syndrome after exogenous surfactant administration: A comparison between two surfactant preparations

Abstract: The effects of two surfactant preparations on lung mechanics have been studied on 24 ventilated premature infants with respiratory distress syndrome (RDS): 13 were given artificial surfactant (Exosurf Neonatal, Burroughs-Wellcome) and 11 natural porcine surfactant (Curosurf, Laboratoire Serono France). Measurements of respiratory system compliance (Cdyn, Crs) and resistance (Rrs) were performed immediately before surfactant administration and repeated 6, 18, 24, 48, and 72 hours later. With Exosurf treatment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…There was no change in R rs 0.5 h [17,19], 1 h [21], 3 h [22] or at different time points after administration of natural surfactant [18,23]. After synthetic surfactant R rs initially remained constant and then increased [23] or decreased, but not before 48 h [24]. There was only one single study with no more than four infants in which C L and R rs were measured at short intervals beginning immediately after administration of natural surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…There was no change in R rs 0.5 h [17,19], 1 h [21], 3 h [22] or at different time points after administration of natural surfactant [18,23]. After synthetic surfactant R rs initially remained constant and then increased [23] or decreased, but not before 48 h [24]. There was only one single study with no more than four infants in which C L and R rs were measured at short intervals beginning immediately after administration of natural surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…Anzueto et al [136] administered nebulized Exosurf® vs. placebo to 725 adults with ARDS secondary to sepsis and found no improvement in any measure of oxygenation and no effect on morbidity or mortality. However, interpretation of these negative results is confounded because both laboratory and clinical studies have documented that Exosurf® has low activity compared to animal-derived surfactants [51, [113][114][115][116][117][142][143][144][145], and aerosolization has not been shown to be as effective as airway instillation in delivering surfactant. Gregory et al [137] reported small benefits in oxygenation in a controlled trial in adults with ARDS who received four 100 mg/kg doses of Survanta®, but with no overall advantage in survival in the 43 surfactant-treated patients studied.…”
Section: Current Studies On Surfactant Replacement Therapy In Patmentioning
confidence: 99%
“…This was reported by Van Lierde et al [12] in premature infants who did not receive exogenous surfactant. In the present population the surfactant deficiency was corrected by porcine surfactant instillation resulting in a rapid increase in Crs as previously described [19]. The increase in Crs 18 h after treatment was not significantly different between groups.…”
Section: Discussionmentioning
confidence: 92%